Assessment of Cutting Profile of AISI 1095 by Using Infrared Radiation Approach - Ashaari Kiprawi, Mohammad; Yassin, Abdullah; Tarmizi Syed Shazali, Syed; Shahidul Islam, M; Azrin Mohd Said, Mohd (International Journal of Engineering and Technology, 2018)
This research paper determines the relationship between cutting edge temperature, depth of cut, cutting speed, cutting forces and flank wear. The cutting edge temperature is determined by using a pyrometer consists of Indium Arsenide (InAs) and Indium Antimonide (InSb) photocells to detect infrared radiation that are released from cutting toolâ€™s edge and cutting forces is measured by using a dynamometer. The machining process experiment is done by end milling the outer surface of AISI 1095 carbon steel. The output signal from the photocell and dynamometer is processed and recorded in the digital oscilloscope. Based on the results, the cutting edge temperature and cutting force increases as the depth of cut increases. Meanwhile, increasing cutting speed resulting in cutting edge temperature increases but decreasing in cutting force due to thermal deformation. Also, existence of progressive flank wear at cutting tool causes an increment in cutting edge temperature and cutting force proportionally.Â Â